Moonlighters: A Product of Deprivation or Aspiration? - Jamal, Muhammad; Crawford, Ronald (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1981)
This study explores the nature of relationships between moonlighting and several dependent variables, such as need fulfillment in work and non-work, mental health, participation in voluntary organizations, job performance, absenteeism, anticipated turnover and flex-time and short work week preferences.